2021
DOI: 10.3390/ijerph182111276
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life and Pain Severity in Older Men with Osteoporosis: Cross-Sectional Study

Abstract: Background: The quality of life in osteoporosis is studied for men rather than for women. Aim of the study was to determine how bone mass density (BMD) relates to life quality components and the severity of pain felt by men affected by osteoporosis. Methods: Presented research is a cross-sectional study. The cohort of 62 men aged 65 to 85 years was divided into a group with osteoporosis (N = 27) and a group without osteoporosis (N = 35). The participants’ quality of life was measured with the Qualeffo41 Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The keratoconus does not seem to affect the general life situation. Other studies on QoL and pain, e.g., in male osteoporosis patients, also showed no reduced overall QoL [28].…”
Section: Influence Of Cross-linkingmentioning
confidence: 80%
“…The keratoconus does not seem to affect the general life situation. Other studies on QoL and pain, e.g., in male osteoporosis patients, also showed no reduced overall QoL [28].…”
Section: Influence Of Cross-linkingmentioning
confidence: 80%
“…found a lower femoral BMD T-score was associated with poorer HRQoL scores in PF, SF, and GH domains of men with osteoporosis [ 12 ]. Another study included 62 old men, and found a lower BMD at distal radius was correlated to impaired quality of life [ 37 ]. A similar correlation was also observed between lumbar BMD and HRQoL in osteoporosis men [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar data were obtained in a study by Nawrat-Szołtysik et al, which included a group of men with osteoporosis. The respondents described their quality of life as moderate (Me = 38 points), and the lowest-rated domain was “Leisure and social activities” [ 21 ]. Similarly, in a study by Drozd et al, postmenopausal women with osteoporosis scored an average of 49.38 points on quality of life, while the worst-rated domain was “General health perception” [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a study by Stanghelle et al, conducted on a group of women with osteoporosis, the level of perceived pain was a factor significantly affecting the subjects’ quality of life in all domains of the QUALEFFO-41 scale [ 34 ]. In contrast, in a study by Nawrat-Szołtysik, pain was not a factor significantly affecting quality of life of men with osteoporosis as measured by the QUALEFFO-41 scale, both in total and in individual domains, except for “General health perception” [ 21 ]. It has been also reported that osteoporotic fractures have the negative effect on respiratory function and impairment, which surely negatively affects the patients’ quality of life [ 35 ].…”
Section: Discussionmentioning
confidence: 99%